الطرق العلاجية لمنع حدوث الورم الدموي بعد عمليات تصنيع الوتيرة - يوسف, يوسف; العلوني, فايز; ناطقي, علي رضا (Latakia University Journal -Medical Sciences Series, 2019)
الوتيرة هي عبارة عن بنية تشريحيه فيزيولوجية لحماية الأنف وقيامه بوظائف حيث أن انحرافها يؤدي إلى عسرة تنفس أنفية و انسداد الأنف وأيضاً يسبب بعض المشاكل الأخرى. كان عدد المرضى في هذه الدراسة 105 مرضى ممن أجريت لهم عملية تصنيع الوتيرة septoplasty حيث تم تقسيمهم بشكل عشوائي إلى فئتين 57 مريض أجريت لهم دكة (كمادات ) وفئة أخرى 48 مريض لم تجر لهم دكة أنفية. ففي الفئة الاولى تم وضع دكة انفية مشبعة بالمراهم بعد العمل الجراحي وفي الفئة الثانية أي بدون دكة أنفية تم استخدام فقط الخياطة ( أي التقطيب ) عبر الوتيرة quilting وتم تقييم النتائج في هاتين الفئتين وحسب النتائج التي حصلنا عليها من تلك الدراسة تبين أن استعمال الخياطة عبر الوتيرة بدل استعمال الدكة داخل الأنف أعطت نتائج مشابهه لتلك التي استعمل فيها دكة أنفية. وإن الخياطة عبر الوتيرة كانت مجدية بسبب قلة الألم والانزعاج للمريض ويمكن أن تكون هذه الخياطة كبديل جيد للدكة داخل الأنف التي تستعمل بعد العمل الجراحي للوتيرة . The objective of this study is to look into the generally accepted standards regarding the materials that should be used, how long the packing should be left in place, or whether or not the indications are lacking. Though its use is widespread, the need for nasal packing is not proven. The septal suturing technique is a valid alternative to intranasal packing following septoplasty. 105 septoplasty patients were selected on a randomized basis to either receive (57 patients) or not receive (48 pareints) nasal packing. The results were compared in both groups. None of the patients in both groups showed septal haematoma and differences in septal perforation mcosal adhesion and post operative bleeding in packing, and non-packing groups were not statistically significant (p > 0.05). According to our findings, there was no significant difference between the result of suture fixation to the nasal septum and that of the nasal pack application. However, the septal suture dose did not cause any discomfort for patients, and septal suture can be a preferred alternative to intranasal packing.